Export Diversification and Economic Growth in Malaysia - Mohammad Affendy, Arip; Lau, Sim Yee; Bakri, Abdul Karim (Munich University Library, 2010)
This paper examines the relationship between export diversification and economic growth in Malaysia. We use annual data from 1980-2007 and time-series techniques of cointegration and Granger causality tests to examine the long-run relationship and dynamic interactions among the variables. The results show the presence of a unique cointegrating vector among the four variables. Consistent with previous studies, we found that export diversification plays significant roles to economic growth in Malaysia. This finding suggests that, in order to sustain future economic growth under the static effect of multilateral and regional trade liberalization, Malaysia should diversify its export commodities and develop greater social and economic cooperation with the rest of the world. As an export- oriented economy, in the long run, export diversification strategy could help stabilizing Malaysia’s export earnings.